EDITORIAL - Palhano Ricarte Oliveira, Angelo; Carreiro Cruz, Francisco Edson; Corrêa Fernandes, Indi Nara; da Rocha Pacheco, Lauro Vinícius; Möller, Mathias Alberto; Alves Teixeira, Michelly; Rossinetti Rufinoni, Priscila (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2017)
Editorial do número 05, volume 09-10, ano 2015.